Segmentation of Consumer Interest Towards Local and Imported Basketball Shoe Products in Bandung City Basketball Communities - Gabriel Ramadhan Emileano Davieri; Apriantono, Tommy; Sri Ramania, Nia (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Basketball shoes are one piece of equipment that determines comfort and the risk of injury that an individual will experience during the game. This research aims to show the segmentation of basketball shoe consumers based on local or imported products in the Bandung city basketball community. The method used in this research is descriptive quantitative, where data is obtained through questionnaires based on demographics, socio-economics, geography, habits or culture, as well as psychographics. The samples taken were 70 individuals using the purposive sampling method, the samples taken were individuals who regularly played basketball in a basketball community in the city of Bandung. Based on the data obtained, imported basketball shoe products are more popular than local basketball shoe products. This is based on greater perceived comfort, a sense of security from the risk of injury, a more attractive model, and the social status obtained when using imported basketball shoe products. The conclusion from this research is that imported basketball shoe products tend to be more popular, so that segmentations such as prestige lover, comfort seeker, attention model and trend follower can be obtained. Local basketball shoe products need to pay more attention to the quality and promotional strategies used, so they will not be left behind by imported shoe products.